KAJIAN TRANSFORMASI SPASIAL DI PERI URBAN KORIDOR KARTASURA-BOYOLALI (UNTUK MEMPERKUAT SUBSTANSI PEMBELAJARAN GEOGRAFI KD MENGANALISIS POLA PERSEBARAN DAN INTERAKSI SPASIAL ANTARA DESA DAN KOTA KELAS XII) - Nugroho, Dimas Prasetyo (Pendidikan Geografi, 2014)
ABSTRACTThe purpose of this study: (1) ) to find out the comparison of constructed and non-constructed lands in Kartasura-Boyolali Corridor in 2004, 2009, and 2013 (2) to find out the development of settlement in Kartasura-Boyolali Corridor in 2004, 2009, and 2013 (3) to find out the settlement pattern in Kartasura-Boyolali Corridor. The unit of analysis used in this study was administrative regional unit of Kartasura-Boyolali Corridor. The approach used in this study was spatial pattern approach and spatial process approach.Considering the result of research on spatial transformation in Kartasura-Boyolali Corridor, it could be concluded that (1) the constructed area width in Kartasura-Boyolali Corridor was 1042.87 Ha in 2004, 1078.88 Ha in 2009, and 1087.28 Ha in 200013, the width of constructed land increased by 3.45% in 2004-2009 time interval and by 0.77% in 2009-2013, overall it increased by 4.25% in 2004-2013 (2) The settlement width in Kartasura-Boyolali Corridor was 740.45 Ha in 2004, 747.52 Ha in 2009, and 770.13 Ha in 2013, the settlement width increased by 0.24% in 2004-2009, 0.75% in 2009-20013 and overall it increased by 4.1% in 2004-2013 (3) The settlement pattern in Kartasura-Boyolali Corridor was protracted clustered medium density in type.Keywords: intercity corridor, peri urban, urban sprawl, spatial transformation